Who Benefits from General Knowledge? - Cristina Bellés Obrero; Emma Duchini (Institute of Labor Economics (IZA), 2020)
While vocational education is meant to provide occupational-specific skills that are directly employable, their returns may be limited in fast-changing economies. Conversely, general education should provide learning skills, but these may have little value at low levels of education. This paper sheds light on this debate by exploiting a recent Spanish reform that postpones students' choice between these two educational pathways from age 14 to 16. To identify exogenous changes in its staggered implementation, we instrument this with the pre-reform across-province variation in the share of students in general education. Results indicate that, by shifting educational investment from vocational to general education after age 16, the reform improves occupational outcomes, and results in a significant rise in monthly wages. The effects are larger after the financial crisis, but are concentrated among middle to high-skilled individuals. In contrast, those who acquire only basic general education have worse long-term employment prospects than vocationally-trained individuals.
Keywords: I26; I28; J24; 330; general versus vocational education; heterogeneous returns; financial crisis